Two Brothers (Ship) certification - Two Brothers (Ship : 1809)
Certification for an American ship sailing between Baltimore, Boston, and Rotterdam with John Skinner as captain.
Collection material in Latin.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Skinner, John, -- Captain; Ship's papers -- 19th century; Baltimore (Md.) -- Commerce; Boston (Mass.) -- Commerce; Maryland -- Commerce; Massachusetts -- Commerce; Netherlands -- Commerce -- History -- 19th century; Rotterdam (Netherlands) -- Commerce; United States -- Commerce -- History -- 19th century